Analysis of Factors that Influence Members' Decisions in Choosing a Sharia Savings and Loans Cooperative (Case Study of KSPPS Mutiara Harapan Jamaah) - Usman, Edi; Ilmiah, Nur; Admayanti, Anita; Lukman, Lukman (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the factors that influence members' decisions in choosing a sharia savings and loan cooperative at Kspps Mutiara Harapan Jamaah Kolaka Regency. This research uses a survey method to determine the factors that influence members' interest in choosing Kspps Mutiara Harapan Jamaah Kolaka Regency using qualitative and quantitative research methods. The sample in this research was all members of the research cooperative, totaling 250 people. Then the data obtained is analyzed in the form of quantitative analysis.TechniqueThe data analysis used is multiple linear regression analysis. The results of this research show that partially, namely the t test, it can be concluded that the trust variable has a significant effect on members' decisions in choosing a sharia savings and loan cooperative. Meanwhile, the variables religiosity and financing procedures do not significantly influence members' decisions in choosing a sharia savings and loan cooperative at Kspps Mutiara Harapan Jamaah Kolaka Regency. The results of the simultaneous test, namely the F test, can be concluded that the variables of trust, religiosity and financing procedures do not significantly influence members' decisions in choosing a sharia savings and loan cooperative at Kspps Mutiara Harapan Jamaah Kolaka Regency.